2003
DOI: 10.1002/mrd.10398
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA heteroplasmy in calves cloned by using adult somatic cell

Abstract: Adult somatic cell cloned calves were produced by somatic cell nuclear transfer prepared by fusion of cultured ear fibroblast from a Holstein cow into enucleated oocytes of Luxi Yellow cow. In order to determinate the source of mitochondrial DNA of cloned calves, we designed the breed-specific PCR primers by aligning the known D-loop sequences of Bos taurus and analyzed the displacement loop sequences of five live cloned calves by breed-specific primers PCR. The results demonstrated that mtDNA originated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The phenomenon of mtDNA heteroplasmy in the sexual hybrid embryo (D. rerio $ · G. rarus #) was also reported in mammal somatic cell cloned embryos (Steinborn 2002;Han et al 2003;Inoue et al 2004). When exploring the development of cloned embryos derived from transgenic common carp (Cyprinus carpio) nuclei and goldfish (Carassius auratus) enucleated eggs, we also found that the mtDNA of donor and receptor co-existed in the cloned embryos before blood-circulation (Sun et al 2005).…”
Section: Disscussionsupporting
confidence: 69%
“…The phenomenon of mtDNA heteroplasmy in the sexual hybrid embryo (D. rerio $ · G. rarus #) was also reported in mammal somatic cell cloned embryos (Steinborn 2002;Han et al 2003;Inoue et al 2004). When exploring the development of cloned embryos derived from transgenic common carp (Cyprinus carpio) nuclei and goldfish (Carassius auratus) enucleated eggs, we also found that the mtDNA of donor and receptor co-existed in the cloned embryos before blood-circulation (Sun et al 2005).…”
Section: Disscussionsupporting
confidence: 69%
“…Previous studies reported numerous cases where iSCNT embryos implant and survive pregnancy but die shortly after birth (Hammer et al . 2001; Han et al . 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the success of viable offspring from Male buffalo Injected 6 9.7 ¥ 10 5 Ϯ 2.0 ¥ 10 5 6.3 ¥ 10 2 Ϯ 1.9 ¥ 10 2 0.07 Fused 7 8.8 ¥ 10 5 Ϯ 1.7 ¥ 10 5 5.9 ¥ 10 2 Ϯ 2.2 ¥ 10 2 0.07 Activated 6 7.7 ¥ 10 5 Ϯ 1.7 ¥ 10 5 5.4 ¥ 10 2 Ϯ 2.4 ¥ 10 2 0.07 Arrested at 8-to 16-cell 9 9.2 ¥ 10 5 Ϯ 2.0 ¥ 10 5 6.2 ¥ 10 2 Ϯ 2.2 ¥ 10 2 0.07 Female buffalo Injected 3 8.2 ¥ 10 5 Ϯ 1.5 ¥ 10 5 1.0 ¥ 10 3 Ϯ 2.2 ¥ 10 2 0.13 Fused 3 8.4 ¥ 10 5 Ϯ 2.4 ¥ 10 5 6.3 ¥ 10 2 Ϯ 1.6 ¥ 10 2 0.08 Activated 3 9.0 ¥ 10 5 Ϯ 1.6 ¥ 10 5 1.1 ¥ 10 3 Ϯ 2.3 ¥ 10 2 0.12 Arrested at 8-to 16-cell 12 7.6 ¥ 10 5 Ϯ 2.3 ¥ 10 5 7.4 ¥ 10 2 Ϯ 3.6 ¥ 10 2 0.10 iSCNT embryos was limited in combining closely related species, as observed in gaur-bovine (Lanza et al 2000), mouflon-sheep (Loi et al 2001), African wild cat-domestic cat (Gómez et al 2004) and gray wolf-domestic dog experiments (Kim et al 2007). Previous studies reported numerous cases where iSCNT embryos implant and survive pregnancy but die shortly after birth (Hammer et al 2001;Han et al 2004). These findings may be a result of inefficient electron transport chain activity due to species differences/divergence (Spikings et al 2006).…”
Section: Mtdna Content Of Buffalo Iscnt Embryosmentioning
confidence: 99%
“…However, other studies report that no detrimental effect of heteroplasmy manifests itself in SCNT embryos or offspring. Evidence of the presence of donor mtDNA during all stages of development and in offspring born from SCNT embryos has been recorded (Hiendleder et al 1999;Do et al 2002;Han et al 2004).…”
Section: The Reconstructed Embryomentioning
confidence: 99%